Pengaruh Model Kooperatif Tipe Teams Games Tournament Untuk Pengembangan Kreativitas Siswa - Didit Darmawan; Munif Mawardi (Konsorsium Dosen Institut Agama Islam Al-Yasini Pasuruan, 2026)
The underlying phenomenon of this research is the persistence of teacher-centered learning processes, lack of student interaction, and limited opportunities for students to develop and express their creative ideas. These conditions lead to student passivity and low learning motivation. This study aims to examine the effect of using the Teams Games Tournament (TGT) cooperative learning model on enhancing student creativity. This study uses a descriptive qualitative approach through library research. The results of the study indicate that the TGT cooperative learning model consistently has a positive and significant impact on enhancing student creativity. This model is able to create an active, enjoyable, and challenging learning atmosphere through a combination of group work, educational games, and academic tournaments, thereby encouraging the participation of all students in the learning process.